ANALISIS RASIO KEUANGAN DALAM MEMPREDIKSI PERTUMBUHAN LABA PERUSAHAAN BARANG KONSUMEN PRIMER DI BURSA EFEK INDONESIA - Siti Mudawanah; Maesaroh (JAD : Jurnal Riset Akuntansi & Keuangan Dewantara, 2025)
Profit growth is an important indicator that shows the success of management in running business operations. However, profit fluctuations that occur in primary consumer goods sector companies raise questions about the factors that influence them. This study aims to analyze the effect of Current Ratio (CR), Debt to Equity Ratio (DER), and Net Profit Margin (NPM) on profit growth in primary consumer goods sector companies listed on the Indonesia Stock Exchange for the period 2021-2024. The population in this study were all primary consumer goods sector companies listed on the Indonesia Stock Exchange for the 2021-2024 period, totaling 132 companies. The sampling technique used purposive sampling method and obtained 63 companies as samples. This study uses a quantitative approach with multiple linear regression analysis methods. The data used is secondary data obtained from the company's annual financial statements. The results of the study Partially the variables Debt to Equity Ratio (DER) and Net Profit Margin (NPM) have a significant effect on profit growth, while Current Ratio (CR) has no significant effect on profit growth. Simultaneously variable Current Ratio (CR), Debt to Equity Ratio (DER), and Net Profit Margin (NPM) have a significant effect on profit growth.